Comparison of Conventional Banks' Financial Performance and Overseas Branches Pre- and Post-Covid-19 - Nurhayati (EAJ (Economic and Accounting Journal), 2024)
This research aims to determine whether there are significant differences in the financial performance of conventional banks and their overseas branches before and during the Covid-19 pandemic in Indonesia. The study focuses on key financial ratios, including the Capital Adequacy Ratio (CAR), Return on Assets (ROA), Operating Expenses to Operating Income (BOPO), and Loan-to Deposit Ratio (LDR). The data spans two periods: pre pandemic (January 2018 to December 2019) and during the pandemic (January 2020 to December 2021). Descriptive statistics reveal that both domestic and overseas banks maintained CAR ratios above 12%, indicating strong risk management capabilities. However, domestic banks showed better resilience in terms of ROA and BOPO during the pandemic, while overseas branches faced greater operational inefficiencies. A series of  statistical tests, including the paired sample t-test and Wilcoxon Signed Rank Test, were  conducted to evaluate the differences in performance. The results indicate significant  differences in CAR, BOPO, and LDR ratios for both domestic and overseas banks before and during the pandemic. Notably, domestic banks had a higher CAR and ROA compared to their overseas counterparts before the pandemic. The findings highlight the varying  degrees of resilience between domestic and international branches, offering valuable  insights into the ability of different types of banks to withstand global economic shocks. These insights contribute to the development of strategies for improving financial stability and crisis management in the banking sector.